Destruction of virus particles via mechanical and chemical virucidal activity of nanocolumnar copper thin films - Keisuke Shigetoh; Yusuke Hirata; Nobuhiko Muramoto; Nobuhiro Ishida (Materials Today Bio)
Human-generated droplets, which facilitate the transmission of viral infections, include large droplets and aerosols. The drying rates of these droplets upon adhesion to a surface vary significantly owing to the wide range of their sizes (∼nine orders of magnitude). Consequently, combating viruses requires distinct strategies under wet and dry conditions. However, studies that account for these two contrasting conditions are lacking. In the present study, we replicated these conditions and investigated the topographical properties of enveloped bacteriophages as an indicator of viral integrity via high-speed atomic force microscopy. Under wet conditions, a reduction in the virus particle volume was observed only on a nanocolumnar copper (NC-Cu) thin film and not on a chemically stable nanocolumnar cupric oxide (NC-CuO) thin film. In contrast, under dry conditions, virus particles lost their shape integrity on both NC-CuO and NC-Cu films. The deformation of virus particles on the NC-CuO film under dry conditions suggests a mechanism distinct from the chemical activity of Cu (i.e., mechanical activity). These results indicate that dry conditions trigger the mechanical activity of nanostructured surfaces. This highlights the significance of nanostructure-induced mechanical activity in virus inactivation under dry conditions, such as those involving viruses in small droplets or aerosols.